Os desafios do uso das tecnologias de informação e comunicação no processo judicial: as respostas do constitucionalismo contemporâneo diante do processo eletrônico - Langner, Ariane (2016)
The recent insertion of the electronic process befalls wrapped in a series of questions, since in relation to the more practical aspects of procedural routine to the most sensitive issues, particularly in relation to the exponential use of the technique, which requires a deep reflection. Alongside this context, it is notorious double face of crisis, which is revealed in a model of the problem of law and the philosophical and interpretive parameter, and, to some extent, prevents the "happening" of decision theory of Constitutionalism Contemporary. This dissertation, based on this situation, seek to answer the following question: to what extent the civil process of electronic nature, to be conceived in the wake of new information and communication technologies (TIC`s), puts at risk what has been She won in terms of the theory of decidability, based on the Constitutionalism Contemporary assumptions? Therefore, the "methodology" approach used is the "method" phenomenological-hermeneutic and, as regards methods of procedure, monographic and historical methods will be adopted. It is concluded that there are risks inherent in the extensive use of technology, which, when used to promote the process of virtualization, deepens the risk of a poor justice meaning, dematerialized, destemporalizada and dehumanized, to strengthen and enhance the hallucinatory search referring quantitative results in practice due to acceleration of pressing technique. The big concern is imminent deepening the gap between factual world (case) and legal world, exacerbating the difficulty of inserting the judge-interpreter in the hermeneutic situation, substantially changing the hermeneutic circle and the ontological difference. It remains, therefore, a long road still to be traveled in order to speak of a real "happening" of Constitutionalism Contemporary decision theory and, therefore, it is essential to discuss / prevent that put into question what has been achieved.